Huck runs amuck! - Taylor, Sean, 1965-; Reynolds, Peter, 1961- (New York : Dial Books for Young Readers, 2011)
The residents of North Skettykolk are no match for a visiting mountain goat with an enormous appetite for flowers.
Kirkus Review
Publisher's Weekly
Kirkus Review, March 2011
Publisher's Weekly, February 2011
2.9
K-3
Keywords: Flowers -- Juvenile fiction; Goats -- Juvenile fiction; Mountain goat -- Juvenile fiction; Flowers -- Fiction; Goats -- Fiction; Humorous stories; Mountain goat -- Fiction; Flowers -- Fiction; Goats -- Fiction; Humorous fiction; Mountain goats -- Fiction; Humorous fiction; Picture books for children